Metal Matrix Composites—The Way Forward - Manoj Gupta (Applied Sciences, 2020)
The magic of the unification of different categories of materials to develop superior materials (composites) with improved functionality was recognized way back by our forefathers and was utilized very well by mother nature to support the dynamic functionality and requirements of both static and moving living organisms [...]